Building a “Deep Fund of Good Will”: Reframing Research Engagement - Passmore, Susan R. (J Health Care Poor Underserved, 2016)
BACKGROUND: The engagement of underrepresented populations in health research has been an ongoing challenge. Yet, the participation of these groups is recognized as key to health equity. METHODS: Semi-structured interviews with 31 experienced investigators successful in the recruitment of underrepresented minorities were analyzed with reference to the concept of social capital to determine: 1) if it is actually in use by successful researchers although, yet unidentified as such; and 2) if the rubric could shed light on new directions especially for those who find it difficult to systematically implement community-engaged recruitment methods. RESULTS: Findings indicate that some aspects of the concept of social capital are being used successfully, but that there are also substantial barriers to its full implementation. CONCLUSION: A lack of enforceable trust and associated institutional support for researchers is a detriment to research engagement. Efforts to remedy this would benefit large research projects, including clinical trials.